Urban Heat Island Appraisal by Historical Building: A Case Study of Gunongan and Kandang in Banda Aceh City (International Journal of Architecture and Urbanism, 2025)
Urban Heat Island (UHI) remains a persistent challenge, primarily driven by the use of dark materials such as asphalt, steel, and brick in urban environments. Although these materials dominate, heritage buildings, particularly in city centers, continue to exist throughout urban areas. This research focuses on the thermal impact of the heritage buildings Gunongan and Kandang in Banda Aceh, Indonesia. These structures, made from limestone and finished with white surfaces, are situated close to the city center, a location where UHI effects are commonly observed. This study evaluates the thermal performance of Gunongan and Kandang to determine their potential contribution to or mitigation of the UHI effect. Data was collected over two days in June 2022, measuring air temperature (Ta), relative humidity (RH), air velocity (Av), globe temperature (Tg), and surface temperature (Ts). The results revealed that the majority of the Ts of Gunongan and Kandang were lower than the surrounding air temperature, with the exception of the dark brick surfaces within Kandang, where Ts reached up to 58°C. The outdoor thermal comfort of the area was also assessed through Physiologically Equivalent Temperature (PET), which ranged from 34°C to 38°C, categorized as warm. The findings indicate that the white limestone surfaces of the buildings were effective in maintaining a lower Ts than Ta, contributing to the reduction of the UHI effect. Additionally, the study shows that shading plays a significant role in lowering urban temperatures as indicated by the mean radiant temperature (Tmrt), derived from the collected thermal data.